Endorsement of HIV misconceptions over time among females and males in Haiti - Roger Antabe; Yujiro Sano (HIV Research & Clinical Practice)
To address high HIV prevalence rates in Haiti, disseminating information about HIV transmission has been emphasized. Yet, after several decades, we do not know how effective HIV information dissemination has been in reducing HIV misconceptions. Using the 2005-06, 2012, and 2016-17 Haiti Demographic and Health Surveys and applying logistic regression, we found nuanced gender dynamics in endorsing HIV misconceptions over time. Among females at the bivariate level, the odds of endorsement of HIV misconceptions in 2012 (OR = 0.87, p < 0.05) and 2016-17 (OR = 0.68, p < 0.001) had declined compared to 2005-06. At the multivariate level, however, we observed that demographic factors suppressed the difference between 2005-06 and 2012, although those in 2016-17 (OR = 0.71, p < 0.001) were still less likely to endorse HIV misconceptions. However, this relationship disappeared once we added behavioral factors (OR = 0.93, p > 0.05). Among males, after controlling for demographic, socioeconomic, and behavioral factors at the multivariate level, those in 2012 (OR = 1.55, p < 0.001) and 2016-17 (OR = 1.24, p < 0.01) were more likely to endorse HIV misconceptions compared to men in 2005-06. We recommend that while improving women’s access to HIV services, it is important to incorporate the HIV needs of males into the National HIV policy priority areas.